Penatalaksanaan Fisioterapi Pada Kasus Down Syndrome Dengan Metode Neuro Development Treatment Di YPAC Surakarta - Fikarin, Ukhti; , Dwi Rosella Komala Sari, SSt.FT.,M.Fis (2017)
Background: Down Syndrome is a chromosomal disorder that is the formation of chromosome 21 (trisomy 21) due to failure of a pair of chromosomes to separate each other during division. Clinical symptoms are often found in children with Down syndrome in the form of developmental delay, mental retardation, and typical physical characteristics. One of the methods that can be given to deal with problems that appear in Down syndrome children is Neuro developmental Treatment (NDT). Purpose: to find out how the management procedures of Neuro Development Treatment for Down syndrome and the benefits of Neuro Develoment Treatment to increase muscle strength and functional ability in children with Down syndrome. Result: After doing therapy as much as 6 times, obtained an increase in muscle strength in lower extremity that is at hip region. Where there is an increase in T5 and T6 which previously had a value of 3 to a value 4. While the evaluation of muscle strength in the upper extremity didn't change. DDST indicates a developmental delay and doesn't change. Conclusion: Neuro Development Treatment (NDT) can increase muscle strength in children with Down syndrome.